Development Of A Sensor Module And Data Logger Capable Of Measuring High Kinematic Parameters In Football - Meamarbashi, Abbas (2007)
INTRODUCTION: Understanding the complexities of segmental movements in sporting activities involving high rotational kinematics is essential for performance enhancement. To date, the underlying mechanisms have been studied using indirect methods of 2 or 3-dimensional videography (Nunome, 2006). However, to the best of our knowledge, no direct method has been reported for measuring high rotational kinematics of the instep kick in football. OBJECTIVES of the present study are: (1) to develop a new sensor module capable of measuring high linear and rotational kinematics of the shank and thigh during an instep kick in the field, (2) to develop a Data Logger software for storing kinematic data in a memory card and a computer software for retrieving and processing the stored data, (3) to determine the reliability and validity of the sensor and Data Logger by comparing its output values with that of a standard isokinetic machine (Biodex) at 500 o/s, 300 o/s and 210 o/s. (4) to determine the applicability and robustness of the device during an instep kick in the field. METHODS: The geometric configuration of the sensor module was based on the principle of differentiations of parallel axis acceleration. Consequently, the sensor module had two dual axes (X-Y) and three mono-axial (2) accelerometers placed 20 cm apart on a printed circuit board with similar axis parallel to each other while the Data Logger had one Triaxial accelerometer. This configuration enabled the capturing of the high linear and rotational acceleration of the shank and thigh in three axes as well as the magnitude of two-dimensional angular velocity. The Data Logger's microcontroller software was written in C language while the computer software was programmed in Delphi and FoxPro. The computer software enabled kinematic parameters (linear, angular accelerations and velocity) and kinetic parameters (force, torque, momentum and power) to be derived from the data recorded by the Data Logger in the field. The validity and reliability of the sensor module of the Data Logger are verified by attaching the sensor module to the Biodex lever arm and recruited five (5) subjects to perform five extension / flexion movements on the Biodex at 500 o/s, 300 °/5 and 210 o/s. The simultaneous output values from the Data Logger and Biodex were recorded and compared statistically using regression analysis and Cronbach's Alpha. In the field, the applicability and robustness of the device were tested by attaching the sensor module to the shank of the dominant leg and the Data Logger at the middle of the thigh. Four (4) instep kicks were performed at an approach angle of 45 o to 60 0. The recorded data stored in the Data Logger was downloaded into the computer to compute the kinetic parameters of force, torque, angular momentum and angular power. The results were statistically analysed using SPSS and presented as mean±SD.